2019
DOI: 10.3390/en12132562
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Analysis Methods for Pulse Decay Tests Considering Gas Adsorption

Abstract: The pulse decay test is the main method employed to determine permeability for tight rocks, and is widely used. The testing gas can be strongly adsorbed on the pore surface of unconventional reservoir cores, such as shale and coal rock. However, gas adsorption has not been well considered in analysis pulse decay tests. In this study, the conventional flow model of adsorbed gas in porous media was modified by considering the volume of the adsorbed phase. Then, pulse decay tests of equilibrium sorption, unsteady… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…We examined closely the intact pressure curves throughout the experiment and found that gas flow in the preferential flow path occurs at the very beginning of the pulse-decay experiment, which finishes within one second based on our observation, and it is much faster than that in the secondary accessible flow path. Thus, the concepts of total and secondary accessible porosity, estimated from Equations (4) and (5), respectively, are proposed in this work to differentiate the two types of the flow path. Figure 4 shows two types of porosity calculated from the test at different pressures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined closely the intact pressure curves throughout the experiment and found that gas flow in the preferential flow path occurs at the very beginning of the pulse-decay experiment, which finishes within one second based on our observation, and it is much faster than that in the secondary accessible flow path. Thus, the concepts of total and secondary accessible porosity, estimated from Equations (4) and (5), respectively, are proposed in this work to differentiate the two types of the flow path. Figure 4 shows two types of porosity calculated from the test at different pressures.…”
Section: Resultsmentioning
confidence: 99%
“…Gas and liquid permeability are different, partially due to the Klinkenberg (gas slippage) effect [1][2][3]. The transient pulse-decay experiments have been frequently applied to measure the permeability of tight porous media [4][5][6][7]. Table 1 chronologically lists representative work of exploring transient flow properties using the pulse-decay method since 1968.…”
Section: Introductionmentioning
confidence: 99%
“…To study the performance of the pulse decay test in the presence of gas adsorption, the numerical simulation method of Han et al [23] was used in this study. Figure 13 shows the pressure equilibrium time considering the gas adsorption effect, where V L is the Langmuir volume [m 3 /kg] and P L is the pressure, respectively [Pa].…”
Section: Effect On the Pressure Equilibrium Timementioning
confidence: 99%
“…Cui et al [22] first considered the gas adsorption effect by modifying the porosity and extended the conventional analysis method to the case of gas adsorption. Han et al [23] considered the effect of the adsorbed phase volume based on Cui's method and proposed the pressure derivative method to analyze the pulse decay test of nonequilibrium adsorption situations.…”
Section: Introductionmentioning
confidence: 99%
“…Reservoir rocks in conventional versions are mainly characterized by absolute permeability above 0.01 mD, while unconventional-below 0.01 mD [1]. Computational fluid dynamic (CFD) gives the opportunity to assess the absolute permeability of the rock, supporting the standard procedure: laboratory measurements of absolute permeability, as gas permeameters [2]. However, it is still challenging to estimate the absolute permeability in tight rocks (unconventional) [3,4].…”
Section: Introductionmentioning
confidence: 99%